Laryngeal mask airway as a rescue device for failed endotracheal intubation during scene-to-hospital air transport of combat casualties. (October 2018) - Shavit, Itai; Aviram, Eliad; Hoffmann, Yoav; Biton, Oded; Glassberg, Elon
Abstract : Background: Advanced airway management of combat casualties during scene-to-hospital air transport is challenging. Because of the short transport time, flight physicians of the Israeli military airborne combat evacuation unit are approved for the use of a laryngeal mask airway (LMA) in the event of failed endotracheal intubation (ETI). The aim of this study was to assess the effectiveness of LMA use during scene-to-hospital transport of combat casualties in Israel. Patients and methods: A retrospective cohort analysis of all combat casualties treated with ETI during scene-to-hospital transport over a 3-year period was carried out. Successful LMA insertion was defined as satisfactory placement of the device on the basis of adequate chest expansion with bag-mask ventilation. Results: The median flight time from scene to hospital was 13 min [interquartile range (IQR): 9–15 min]. Sixty-five casualties underwent ETI attempts, 47 successful and 18 failed. All 18 casualties who had failed ETI underwent LMA insertion as a rescue treatment. Six casualties suffered from traumatic brain injury, six had firearm injuries, two had blast injuries, and two had inhalational injuries. LMA insertion was successful in 16/18 (88.9%) casualties, 14 survived to hospital discharge, whereas two were declared dead upon hospital arrival. Two cases of LMA insertion were unsuccessful, but patients survived to hospital discharge. Among the 16 successful cases, the median oxygen saturation on scene-pickup before LMA insertion and on hospital-handover with LMA in place were 90% (IQR: 84–96%) and 98% (IQR: 96–99%), respectively ( P <0.0001, the 95% confidence interval for difference between medians was 4–11). Conclusion: The findings of this study suggest that in the event of failed ETI, combat casualties can be treated effectively with LMA during a short scene-to-hospital transport time.